Neuropsychiatric symptoms among older people in Central Africa - (:unkn) unknown (My University, 2019)
Neuropsychiatric symptoms are common among older adults with or without cognitive disorders. In sub-Saharan Africa, few population-based studies are focused on these symptoms and to our knowledge no study was conducted in Central Africa. Our main objectivewas to improve the knowledge of neuropsychiatric symptoms in Central Africa (Central African Republic: CAR and Republic of Congo: ROC). Specifically we aimed at describing the neuropsychiatric symptoms, their severity, their distress and associated factors; 2) evaluating the association between neuropsychiatric symptoms and Apolipoprotein E ε4; 3) evaluating the association between neuropsychiatric symptoms, mortality and cognitive decline among older adults We performed the studies, using data from the EPIDEMCA and EPIDEMCA-FU programmes. The prevalence of neuropsychiatric symptoms was 63.7% (95%CI: 59.5-67.8).The overall median score of severity was 9 [IQR: 6-12] and the overall median score of distress was 7 [IQR: 4-10]. Living in Gamboma (rural ROC), normal hearing and having friends in the community were protective while female sex, dementia, dependent personality, and physical disability were risk factors for neuropsychiatric symptoms. Delusions, depression, apathy, disinhibition and aberrant motor behavior were specifically associated with dementia. We are not able to confirm the relationship between neuropsychiatric symptoms and Apolipoprotein E ε4. Neuropsychiatric symptoms were associated with mortality after two years of follow-up but not associated with cognitive decline. This thesis allowed us to improve the knowledge of behavioral disorders in Central Africa. Due to their burden among caregivers, a better management of these symptoms must be performed.
Keywords: African Research